The research of force characteristics of the rotary working body for inter-row tillage - Беловол, Светлана Аналольевна (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis of power characteristics, acting on a rotary body with a vertical rotation has been carried out. It has been determined that the rotation of discs in different directions will be rational in terms of energy consumption and quality of inter-row tillage. According to the results of a kinematic analysis it has been determined that with the growth of relations between a rotary and a translational velocity of the working body its draft resistance decreases. The theoretical results are allowed justifying the technical solution of the rotary body and developing a pilot unit for inter-row tillage. Experimental studies of the dependence of the working body draft resistance of the proposed design on its parameters have been conducted. A statistical processing of experimental data has been made. The results of theoretical studies have been experimentally proved, and the optimal values of angular and translational velocity of the rotary body have been substantiated. Using the rotary bodies of the proposed design with reasonable parameters will provide a high quality inter-row tillage for rational indicators of energy consumption and process efficiency.